PV energized EV motor using improved dolphin pod optimized PI controller with high gain Z source converter - Santhoshi, B Kavya; Kishore, Dondapati Ravi; Govindu, Anusuri Venkata Mani; Kumar, Bhairi Vinod; Rohit, Kakana Boyina (Revista Brasileira de Engenharia de Biossistemas, 2026)
Photovoltaic (PV) based Electric Vehicle (EV) charging faces challenges of low voltage output, unstable supply, and limited converter performance under changing atmosphere condition. Hence, this work aims to develop a Permanent Magnet Synchronous Motor (PMSM) driven EV charging efficiency and stability using a novel converter and control approach. The major objective of this approach is to attain high efficient EV performance with improved stability and reliability. A High Gain Switched Quasi Z Source Converter (HG-SqZSC) is utilized for boosting the output voltage of PV with higher efficiency and increased voltage gain. An Improved Dolphin Pod (IDP)- optimised Proportional Integral (PI) controller is deployed to achieve a stable power output with increased convergence speed. On the other hand, during insufficient power supply or abnormal weather conditions, a three-phase grid and battery act as the supplementary power source, thereby providing continuous power supply required for PMSM motor-driven EV. Moreover, to validate the working and efficiency of the proposed PV-energized EV motor, MATLAB/Simulink is utilized which states that, the developed system ensures to attain higher efficiency (93.3%), Voltage gain (15) and reduced Total Hormonic Distortion (THD) (0.63%). Thus, it leads to less environmental pollution with constant EV charging systems even under varying circumstances.